Hybrid solid‐phase extraction to overcome interference due to phospholipids for determination of neratinib in human plasma using UPLC–MS/MS - Shah, Priyanka A.; Sharma, Vinay S.; Vanol, Pravin G.; Sanyal, Mallika; Shrivastav, Pranav S. (Biomedical chromatography, 2022)
A reliable and robust bioanalytical method was developed to quantify neratinib, a tyrosine kinase inhibitor in human plasma, using UPLC–MS/MS. The extraction of neratinib and its deuterated internal standard, neratinib‐d6, was successfully performed on hybrid solid‐phase extraction ultra‐cartridges to remove the interference of phospholipids and proteins. Chromatographic analysis was performed on a UPLC BEH C18 (50 × 2.1 mm, 1.7 μm) column using 0.1% formic acid and acetonitrile under gradient conditions. The total analysis time was 1.5 min. Neratinib was quantified using electrospray ionization source operated in the positive‐ion multiple reaction monitoring mode. The mass transitions of neratinib and neratinib‐d6 were m/z 557.3/112.1 and m/z 563.1/118.2, respectively. The linear concentration range for neratinib was 0.5–500 ng/mL, which adequately covers concentration levels expected in real subject samples. The assay was extensively validated for various validation parameters following standard guidelines for a bioanalytical assay. The intra‐ and inter‐batch precision was ≤4.6%, and neratinib was found to be stable under various stability conditions. The mean internal standard–normalized matrix factor and recovery were 0.997 and 95.4%, respectively. The validated method was successfully applied to a pharmacokinetic study in healthy subjects with different doses.